RUMUSAN STRATEGI DALAM UPAYA MENINGKATKAN KEPUASAN PASIEN RAWAT JALAN INSTALASI FARMASI RUMAH SAKIT MATA DR. YAP YOGYAKARTA BERDASARKAN ANALISIS SWOT - , Fina Aryani, Prof. Dr. Lukman Hakim, M.Sc., Apt. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Nowadays the health development in Indonesia is start to emphasize on the improvement of health service quality, which the quality of the service is orientated on costumerâs satisfactions in order to keep exist on the global competition. Therefore, pharmacy department as one of the health service provider has to arrange the specific purpose along with strategic step to reach their target which is patientâs satisfaction. A descriptive study was done. The data were collected qualitatively through interviewing subjects, and also quantitatively using questionnaire to inquire patientâs satisfaction with Servqual analysis, working spirit scale condition, and Eye Hospital Pharmacy Department Dr. Yapâs workerâs satisfaction as supporting data. The internal and external environments were analyzed based on collected data, followed by Strength, Weakness, Opportunities, and Threats (SWOT) analysis. The result was used as a base to formulate strategies to improve Pharmacy Department of Dr. Yap Eye Hospital Yogyakarta through Quantitative Strategic Planning Matrix (QSPM) test to order priorities of the chosen strategies. Analysis of outpatient satisfactions : the patientâs expectation about the work of hospital pharmacy department employees was higher so appear the negative gap on each dimension which mean that yet patients is satisfied with the work of hospital pharmacy department. Gap point dimension of services from the highest to the lowest in a row, responsiveness (-0,74), assurances (-0,62), emphaty (-0,60), reliability (- 0,51), tangibles (-0,32). Based on SWOT analysis, Eye Hospital Pharmacy Department Dr. Yap Yogyakarta has bigger opportunity (1,54) rather than the threat (1.06) and has strength (1.77) which bigger than weakness (1,18) it means Pharmacy Department of Dr. Yap Eye Hospital Yogyakarta could fulfill the expectations of the patients. Alternative strategy which taken by Pharmacy Department of Dr. Yap Eye Hospital Yogyakarta to fulfill the patientâs expectation is making additional hospital pharmacy department programs which related with eye health, human resource development whether it quality or quantity, perfecting the policy about human resource development of hospital pharmacy department.